Molecular identification of the stem rust resistance genes in the introgression lines of spring bread wheat - O. A. Baranova; S. N. Sibikeev; A. E. Druzhin (Вавиловский журнал генетики и селекции)
A total of 57 introgression lines and 11 cultivars of spring bread wheat developed by All-Russian Institute of Plant Protection and cultivated in the Volga Region were analyzed. The lines were obtained with the participation of CIMMYT synthetics, durum wheat cultivars, direct crossing with Agropyron elongatum (CI-7-57) and have introgressions from related species of bread wheat, namely translocations from Ag. elongatum (7DS-7DL-7Ae#1L), Aegilops speltoides (2D-2S), Ae. ventricosum (2AL-2AS-2MV#1), Secale cereale (1BL-1R#1S), 6Agi (6D) substitution from Ag. intermedium and triticale Satu. Cultivars and lines were assessed for resistance to Saratov, Lysogorsk, Derbent and Omsk stem rust pathogen populations (Puccinia graminis f. sp. tritici), and analyzed for the presence of the known Sr resistance genes using molecular markers. The analysis of the cultivars’ and lines’ resistance to the Saratov pathogen population in the field, as well as to Omsk, Derbent and Lysogorsk populations at the seedling stage, showed the loss of efficiency of the Sr25 and Sr6Agi genes. The Sr31 gene remained effective. Thirty one wheat lines out of 57 (54.4 % of samples) were resistant to all pathogen populations taken into analysis. The Sr31/Lr26, Sr25/Lr19, Sr28, Sr57/Lr34 and Sr38/Lr37 genes were identified in the introgression lines. The Sr31/Lr26 gene was identified in 19 lines (33.3 % of samples). All lines carrying the 1RS.1BL translocation (Sr31/Lr26) were resistant to all pathogen populations taken into analysis. The Sr25/Lr19 gene was identified in 49 lines (86 %). The gene combination Sr31/Lr26+ Sr25/Lr19 was identified in 15 lines (26.3 %). The gene combinations Sr38/Lr37+Sr25/Lr19, Sr57/Lr34+Sr25/Lr19 and Sr31/Lr26+Sr25/Lr19+Sr28 were identified in 3 introgression lines. These three lines were characterized by resistance to the pathogen populations studied in this work. The Sr2, Sr24, Sr26, Sr32, Sr36 and Sr39 genes were not detected in the analyzed wheat lines.